Silicon carbon material as well as preparation method and application thereof

By introducing transition metal salt catalyzing the in-situ growth and carbon coating technology of carbon nanotubes in silicon carbon materials, the problems of high lithium ion diffusion impedance and uneven dispersion of carbon nanotubes are solved, and the battery performance of silicon carbon materials is significantly improved.

CN119695103APending Publication Date: 2025-03-25SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411846848.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In battery applications, existing silicon carbon materials have a slow charge and discharge speed due to the high diffusion impedance of lithium ions and uneven dispersion of carbon nanotubes, which limits the improvement of material performance.

Method used

By introducing transition metal salts into the porous carbon-supported silicon matrix, the in-situ growth of carbon nanotubes is catalyzed, and the dispersion of carbon nanotubes is improved through carbon coating technology, avoid catalyst agglomeration, and promote the growth of single-wall carbon nanotubes.

Benefits of technology

The uniform dispersion of carbon nanotubes in silicon carbon materials is achieved, the conductivity, specific surface area and voltage resistance of the material are improved, and the rate performance and cycle performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189495650000111
    Figure BDA0005189495650000111
  • Figure BDA0005189495650000151
    Figure BDA0005189495650000151
  • Figure BDA0005189495650000152
    Figure BDA0005189495650000152
Patent Text Reader

Abstract

The invention discloses a silicon-carbon material as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, reacting a mixed solution containing a porous carbon-loaded silicon substrate, transition metal salt and a solvent with an alkaline reagent to obtain a first precursor; wherein the transition metal salt comprises divalent salt and trivalent salt of transition metal; wherein the reaction is carried out under a protective atmosphere; s2, performing chemical vapor deposition on the first precursor by adopting a carbon source, and growing a carbon nanotube in situ to obtain a second precursor; and S3, carrying out carbon coating on the second precursor to obtain the silicon-carbon material. According to the preparation method, agglomeration of the catalyst can be effectively avoided, growth of single-walled carbon tubes in the silicon-carbon material is promoted, the carbon tubes are dispersed more uniformly, and the performance of the obtained silicon-carbon material can be further comprehensively optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon material and a preparation method and application thereof. Background Art

[0002] The application of silicon-carbon materials is the most important technology for improving battery energy density so far. In just two years, this technology has increased the energy density of consumer batteries from 500wh / L to 800wh / L, and is moving towards 1000wh / L. According to theoretical calculations, if the negative electrode material of a traditional 5000mAh lithium-ion battery can be replaced with silicon-carbon materials (silicon content is 52%), the energy density of the battery can be increased to about 8000mAh or more, which means that the battery life of traditional mobile phones can be increased by at least 50%.

[0003] However, although the gram capacity of silicon-carbon materials is huge, and the lithium insertion potential is about 0.4v, which is much higher than the 0.1v of graphite, it should have better rate performance and the ability to inhibit lithium precipitation. However, in fact, due to the lithium insertion mechanism, alloy-type lithium storage is more susceptible to the diffusion of lithium ions; such as laser etching technology, double-layer coating technology, low ion diffusion, multi-stage combination of binders and supporting catalysts, as well as high-concentration lithium salt, high dielectric constant, high voltage system electrolyte formulation technology, although it can increase the rate of ion diffusion to a certain extent, but in actual applications, the 6% silicon-carbon material 6000mah charge and discharge speed is only half of that of traditional graphite. The main reason is that when the charging power is too high, it is easy to cause lithium precipitation of the electrode, which makes the silicon-carbon material that can theoretically reduce lithium precipitation unsatisfactory in practice.

[0004] At present, for raw material factories, growing carbon nanotubes on the surface of silicon-carbon materials is a more feasible way to reduce the ion diffusion resistance of silicon-carbon materials.

[0005] In the previous carbon nanotube doping process, carbon nanotubes are often doped into the precursor or wrapped on the outer surface of the silicon-carbon material. However, the effect is limited and is restricted by the dispersion inhibition of carbon nanotubes, resulting in limited performance increase and cost reduction, which is not conducive to the large-scale mass production of silicon-carbon materials.

[0006] At present, simple loading methods such as impregnation are often used to load catalysts that can catalyze the growth of carbon nanotubes on the surface of silicon-carbon materials, followed by calcination and reduction. This is simple and feasible and conducive to mass production. However, when using the traditional impregnation method to grow carbon nanotubes, the catalyst is very likely to agglomerate, resulting in uneven distribution of the grown carbon nanotubes, inhibiting the growth of single-walled carbon nanotubes, and growing multi-walled carbon nanotubes, chiral carbon nanotubes, semiconductor carbon nanotubes, etc. with more defects. It is difficult to control as a whole, and the performance improvement of the final silicon-carbon material still needs to be improved. Summary of the invention

[0007] In order to overcome the above defects of existing silicon-carbon materials loaded with carbon nanotubes, the present invention provides a silicon-carbon material and a preparation method and application thereof. The preparation method can effectively avoid the agglomeration of catalysts during the preparation process, promote the growth of single-walled carbon nanotubes in the silicon-carbon material, and the carbon nanotubes are more evenly dispersed, and the performance of the obtained silicon-carbon material can be further comprehensively optimized.

[0008] To achieve the above purpose, the present invention adopts the following technical solution.

[0009] The present invention provides a method for preparing a silicon-carbon material, and the method for preparing the silicon-carbon material comprises the following steps:

[0010] S1, a mixed solution containing a porous carbon-supported silicon substrate, a transition metal salt and a solvent, reacts with an alkaline reagent to obtain a first precursor;

[0011] Wherein, the transition metal salt includes divalent salt and trivalent salt of transition metal;

[0012] Wherein, the reaction is carried out under a protective atmosphere;

[0013] S2, using a carbon source to perform chemical vapor deposition on the first precursor to in-situ grow carbon nanotubes to obtain a second precursor;

[0014] S3. Carbon-coating the second precursor to obtain the silicon-carbon material.

[0015] In the present invention, in step S1, the transition metal salt reacts with an alkaline reagent to generate nano transition metal oxides. During the reaction, the nano transition metal oxides are generated preferentially in the mesopores and macropores of the porous carbon-supported silicon matrix, and then on the surface.

[0016] In the present invention, the transition metal salt may be a soluble salt of a transition metal conventional in the art that can catalyze the growth of carbon nanotubes in the form of an oxide or a single substance.

[0017] In some embodiments, in step S1, the transition metal salt includes one or more of an iron salt, a nickel salt, and a cobalt salt.

[0018] In some preferred embodiments, in step S1, the transition metal salt includes a divalent salt and a trivalent salt of iron; the molar ratio of the divalent salt and the trivalent salt of iron is preferably (2-4): 1. Studies have shown that when divalent and trivalent salts of iron are used, paramagnetic nano-iron tetroxide can be generated, which is not easy to agglomerate, is more conducive to the deposition of carbon sources to grow single-walled carbon nanotubes, and has a better catalytic carbon nanotube growth rate.

[0019] In some embodiments, in step S1, the transition metal salt includes one or more of transition metal hydrochlorides, transition metal sulfates, transition metal acetates, and transition metal citrates.

[0020] In some embodiments, in step S1, the transition metal salt includes ferrous sulfate and ferric chloride; wherein the molar ratio of the ferrous sulfate to the ferric chloride is preferably (2-4):1.

[0021] In some preferred embodiments, in step S1, the content of the transition metal salt is 0.03-0.3 mol / L, for example, 0.12 mol / L, and the content is the number of moles of the transition metal salt contained in 1 L of the solvent.

[0022] In some embodiments, in step S1, the mixed solution also includes a complexing agent. Based on the complexing effect of the complexing agent, the nano-size and uniformity of the transition metal oxide in the reaction can be greatly promoted, and its agglomeration phenomenon can be further reduced. In addition, when the complexing agent is added, the complexing agent is coated on the surface of the porous carbon-loaded silicon substrate, and some oxygen-containing groups will be retained after carbonization. The hydrogen bonds and van der Waals forces between the complexing agent and the polar binder are stronger, and the bonding effect is stronger, which can inhibit powder loss; when the complexing agent contains metal atoms, it is easy to change the smoothness of the subsequent coated carbon layer after carbonization, increase the contact degree between the subsequent coated carbon layer and the surface of the porous carbon-loaded silicon substrate, and is more conducive to the improvement of the strength of the subsequent coated carbon layer; and the doping of metal atoms in the coated carbon layer has the effect of transforming the carbon material into amorphous carbon, changing the disordered structure of the amorphous carbon material, and effectively inhibiting the buffering stress and expansion of the surface of the silicon-carbon material, and improving the pressure resistance of the silicon-carbon material.

[0023] The complexing agent preferably includes an organic acid and a salt thereof, more preferably includes one or more of acetic acid, citric acid, EDTA and a salt thereof, for example, includes one or more of ferric acetate, sodium acetate, ferric citrate, sodium citrate and EDTA.

[0024] Wherein, the mass ratio of the complexing agent to the porous carbon-supported silicon substrate is preferably 1:(5-1000), for example 1:10.

[0025] In the present invention, in step S1, the alkaline reagent may include a weak base reagent and / or a strong base reagent.

[0026] In some embodiments, in step S1, the alkaline reagent is ammonia water. The concentration of the ammonia water is preferably 1-10%, for example 5%. In the present invention, the concentration of the ammonia water refers to the mass percentage of the solute in the ammonia water to the total mass of the ammonia water.

[0027] In some embodiments, in step S1, the mass ratio of the alkaline reagent to the mixed solution is (1-10):100.

[0028] In some embodiments, in step S1, the alkaline reagent is added dropwise to the mixed solution, and the dropping speed of the alkaline reagent is 5-50 mL / min, for example, 10 mL / min.

[0029] In some embodiments, in step S1, the solvent is deionized water.

[0030] In some embodiments, in step S1, the mass ratio of the porous carbon-supported silicon substrate to the solvent is 1:(5-50), for example, 1:10.

[0031] In some embodiments, in step S1, the protective atmosphere includes one or more of an inert atmosphere, a reducing atmosphere, and a carbon dioxide atmosphere, for example, includes one or more of nitrogen, argon, helium, hydrogen, and carbon monoxide.

[0032] In some embodiments, in step S1, the reaction is carried out under stirring conditions.

[0033] Wherein, the stirring speed is preferably 100-1000r / min, for example 300r / min.

[0034] In the present invention, the porous carbon-supported silicon substrate may be conventional in the art, generally comprising porous carbon and silicon, wherein the silicon is distributed in the pores and / or on the surface of the porous carbon; the porous carbon-supported silicon substrate comprises mesopores and macropores.

[0035] The porous carbon-supported silicon substrate of the present invention can be prepared by conventional methods in the art.

[0036] In some embodiments, the method for preparing the porous carbon-supported silicon substrate comprises: depositing silicon on porous carbon to obtain the porous carbon-supported silicon substrate.

[0037] The silicon source for the silicon deposition is preferably silane (general formula: Si n H 2n+2 ), the silane may include monosilane (SiH4), disilane (Si2H6), trisilane (Si3H8) and tetrasilane (Si4H 10 )

[0038] Preferably, during the silicon deposition process, the silicon source and the carrier gas are introduced simultaneously. The volume ratio of the silicon source to the carrier gas is 1:(2-6), for example, 1:4. In the present invention, the porous carbon may be conventional porous carbon in the art.

[0039] In some embodiments, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1200-3000m 2 / g, ② micropores account for 60-100%, ③ mesopores and above account for 0-40%, ④ pore volume is 0.7-1.5cm 3 / g.

[0040] In some specific embodiments, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1890 m 2 / g, ② micropores account for 85.3%, ③ mesopores and above account for 14.7%, and ④ pore volume is 1.32cm 3 / g.

[0041] In the present invention, the porous carbon can be prepared by conventional methods in the art. The carbon source of the porous carbon can include one or more of resin, sucrose, glucose, fructose, starch, cellulose, triglyceride, fatty acid, hemicellulose, lignin and asphalt, preferably resin, more preferably phenolic resin.

[0042] In some embodiments, the porous carbon in the porous carbon-supported silicon matrix is ​​prepared using phenolic resin as a carbon source.

[0043] In some specific embodiments, the method for preparing porous carbon comprises the following steps:

[0044] (1) spray drying a slurry containing a phenolic resin to obtain a carbon material precursor;

[0045] (2) carbonizing the carbon material precursor to obtain a porous carbon precursor;

[0046] (3) Activating the porous carbon precursor to obtain porous carbon.

[0047] In step (1), the slurry may further include a curing agent and a solvent; the curing agent is, for example, hexamethylenetetramine, and the solvent is, for example, ethanol.

[0048] In step (2), the carbonization method may be a conventional carbonization method in the art, such as a staged heat treatment; preferably, the carbonization includes the following stages:

[0049] The first stage: heating to 200℃ at a heating rate of 4℃ / min and keeping the temperature for 60min;

[0050] The second stage: heat up to 652°C at a heating rate of 4°C / min and keep warm for 60 minutes.

[0051] In step (2), the carbonization may be performed under an inert atmosphere, and the inert atmosphere preferably comprises one or more of nitrogen, helium and argon.

[0052] In step (3), the activation method can be a conventional activation pore-forming method in the art, such as deactivation or gas activation, preferably gas activation; the gas source of the gas activation is preferably carbon dioxide.

[0053] In some embodiments, in step S1, the surface of the porous carbon-supported silicon substrate is coated with a passivation layer; the passivation layer preferably includes a carbon layer and / or an oxide layer. The passivation layer can passivate the activity of silicon in the porous carbon-supported silicon substrate to a certain extent, preventing unnecessary side reactions from occurring.

[0054] In some embodiments, the preparation method of coating the passivation layer is to perform chemical vapor deposition using a deposition gas.

[0055] Wherein, the deposition gas preferably includes a carbon source, and more preferably also includes a protective gas. The carbon source preferably includes one or more of alkynes (such as acetylene), alkanes, alkenes, aromatic compounds (such as one or more of anthracene, naphthalene and lignin) and carbohydrates (such as one or more of glucose, cellulose and hemicellulose). The protective gas preferably includes one or more of nitrogen, helium and argon.

[0056] The ventilation volume of the deposition gas is preferably 0.1-10 L·kg -1 ·min -1 , for example 5L·kg -1 ·min -1 The unit meaning of the ventilation rate is the volume of the deposition gas introduced per minute and per kilogram of the solidified material in the current step.

[0057] Wherein, the chemical vapor deposition time is preferably 2-20 hours.

[0058] The temperature of the chemical vapor deposition is preferably 400-800°C, such as 500°C.

[0059] Specifically, when the deposition gas includes the carbon source and the protective gas, the volume ratio of the carbon source to the protective gas is, for example, 20:80.

[0060] In some embodiments, in step S1, the reaction further includes alcoholization and drying steps.

[0061] The alcoholization step can further increase the degree of reaction of the transition metal salt to form the transition metal oxide.

[0062] The alcoholization temperature is preferably 60-100°C, such as 90°C.

[0063] The alcoholization time is preferably 3-12 hours, such as 5 hours.

[0064] The drying temperature is preferably 100-250°C, for example 200°C.

[0065] The drying is preferably performed until the particle size of the obtained particles is 4-20 μm, for example 8 μm.

[0066] Wherein, the drying is preferably carried out in an inert atmosphere; the inert atmosphere preferably includes one or more of nitrogen, helium and argon.

[0067] The drying speed is preferably 0.1-10 kg / h, for example 1 kg / h.

[0068] The drying method is preferably spray drying or vacuum drying.

[0069] In some embodiments, in step S1, the reaction further includes the steps of filtration and washing, and the washing is preferably performed with deionized water.

[0070] In some embodiments, in step S1, the particle size of the first precursor is 4-20 μm, for example, 8 μm.

[0071] In the present invention, in step S2, the first precursor is subjected to chemical vapor deposition using a carbon source. In this process, the transition metal oxide and / or transition metal element in the first precursor can catalyze the in-situ growth of carbon nanotubes. While the carbon nanotubes are grown in-situ, a carbon coating process is simultaneously performed. At this time, the grown carbon nanotubes can grow in the form of being embedded in the carbon layer. After protruding out of the carbon layer, it is helpful to carbon coat again, accelerate the coating speed, and thicken the carbon layer.

[0072] In some embodiments, in step S2, before the chemical vapor deposition, a step of reducing the first precursor is also included. The nano transition metal oxide is reduced to obtain a nano transition metal element, which can further reduce the agglomeration phenomenon and ensure the in-situ growth of single-walled carbon nanotubes.

[0073] The reduction temperature is preferably 400-800°C, such as 550°C.

[0074] The reduction is preferably carried out in a reducing atmosphere, such as hydrogen; the ventilation volume of the reducing atmosphere is preferably 0.1-10 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 The unit meaning of the ventilation rate is the volume of the reducing atmosphere introduced per minute and per kilogram of the solidified material in the current step.

[0075] The reduction time is preferably 30-300 min, for example 120 min.

[0076] In some embodiments, in step S2, the carbon source includes one or more of alkynes (such as acetylene), alkanes, olefins, aromatic compounds (such as one or more of anthracene, naphthalene and lignin) and carbohydrates (such as one or more of glucose, cellulose and hemicellulose).

[0077] In some embodiments, in step S2, the ventilation rate of the carbon source is 2-10 L·kg -1 ·min -1 The unit of ventilation volume means the volume of the carbon source introduced per minute and per kilogram of solidified material in the current step.

[0078] In some embodiments, in step S2, the chemical vapor deposition time is preferably 60-180 min, for example 120 min.

[0079] In some embodiments, in step S2, the temperature of the chemical vapor deposition is preferably 500-700°C, such as 550°C.

[0080] In some embodiments, in step S2, the chemical vapor deposition further includes the steps of pickling and drying.

[0081] The purpose of the pickling is to remove transition metals. The pickling step is preferably carried out with hydrochloric acid; the mass ratio of the hydrochloric acid to the product obtained by the reaction is (5-50):1, for example 10:1.

[0082] The drying method is preferably spray drying or vacuum drying.

[0083] In some embodiments, in step S2, the particle size of the second precursor is 4-20 μm, for example, 8 μm.

[0084] In the present invention, in step S3, the carbon coating can be performed using conventional carbon coating methods in the art.

[0085] In some embodiments, in step S3, the carbon coating comprises the following steps: chemical vapor deposition of the second precursor using a carbon source.

[0086] The carbon source preferably includes one or more of alkynes (such as acetylene), alkanes, olefins, aromatic compounds (such as one or more of anthracene, naphthalene and lignin) and carbohydrates (such as one or more of glucose, cellulose and hemicellulose).

[0087] The ventilation volume of the carbon source is preferably 0.1-10 L kg-1 ·min -1 , for example 2L·kg -1 ·min -1 The unit of ventilation volume means the volume of the carbon source introduced per minute and per kilogram of solidified material in the current step.

[0088] The chemical vapor deposition time is preferably 300-600 min, for example 480 min.

[0089] The temperature of the chemical vapor deposition is preferably 400-800°C, such as 550°C.

[0090] The present invention also provides a silicon-carbon material, which is prepared by the method for preparing the silicon-carbon material as described above.

[0091] The present invention also provides a use of the silicon-carbon material as described above in an electrochemical device.

[0092] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0093] The reagents and raw materials used in the present invention are commercially available.

[0094] The positive and progressive effects of the present invention are:

[0095] The present invention introduces transition metal salts, i.e., precursors of catalysts catalyzing the growth of carbon nanotubes, into a porous carbon-supported silicon matrix. During the reaction, nanoscale metal oxides are generated preferentially in the mesopores and macropores of the porous carbon, which can effectively improve the catalyst agglomeration phenomenon, thereby promoting the subsequent in-situ growth of single-walled carbon tubes. After combined with the final carbon coating, the electrical conductivity, specific surface area, tap density, compressive strength and other properties of the obtained silicon-carbon material can be comprehensively optimized; after being used in batteries, the volume energy density, rate performance and cycle performance and other properties can be further comprehensively optimized. DETAILED DESCRIPTION

[0096] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0097] In the following examples and comparative examples, the preparation of the porous carbon-supported silicon substrate includes the following steps (the overall steps are denoted as S0):

[0098] (1) Preparation of carbon material precursor:

[0099] 1 kg of phenolic resin (2153 type, provided by Hubei Hengye Technology Co., Ltd.), 2 kg of ethanol, and 60 g of hexamethylenetetramine (HMT) were mixed and homogenized with a high-speed dispersing homogenizer at a speed of 2000 r / min for 60 min. Spray drying was performed at 130° C. until the particle diameter was 8 μm.

[0100] (2) Preparation of porous carbon precursor:

[0101] The spray-dried powder was placed in a rotary furnace with a rotation speed of 10 r / min and a nitrogen atmosphere gas supply rate of 1 L·kg -1 min -1 , carbonization is carried out: the first stage: the temperature is increased at a heating rate of 4℃ / min for 50min, and the temperature is increased to 200℃ and kept for 1h. The main purpose is to make the phenolic resin cross-linked; the second stage: the temperature is increased at a heating rate of 4℃ / min for 113min, and the temperature is increased to 652℃ and kept for 1h.

[0102] (3) Preparation of porous carbon:

[0103] Activated in CO2 atmosphere, activation time is 9h, gas supply rate is 2L·kg -1 min -1 The temperature in the furnace was 550°C, and porous carbon was obtained. The specific surface area of ​​the porous carbon was 1890 m 2 / g, micropores account for 85.3%, mesopores and above account for 14.7%, and the pore volume is 1.32cm 3 / g.

[0104] (4) Silicon deposition:

[0105] The atmosphere was switched to monosilane containing carrier gas (20% monosilane and 80% nitrogen by volume) for chemical vapor deposition at 500 °C for 10 h with a ventilation volume of 15 L kg -1 ·min -1 .

[0106] (5) Coating passivation layer:

[0107] The atmosphere was then switched to acetylene containing a carrier gas (20% acetylene and 80% nitrogen by volume) for chemical vapor deposition with a ventilation volume of 5 L kg -1 ·min -1 , continue deposition at 500 °C for 2 h, and then cool to room temperature 25 °C.

[0108] Example 1

[0109] S1. Preparation of the first precursor:

[0110] 1 kg of the porous carbon-supported silicon substrate prepared in step S0 was immersed in 10 kg of deionized water, and after adding 100 g of sodium citrate as a complexing agent, 0.2-1.6 mol of ferrous sulfate was added, and ferric chloride was added at a molar ratio of ferrous sulfate to ferric chloride of 2:1. Then 1 kg of 5% ammonia water was added at a dropping speed of 10 mL / min. After the addition was completed, alcoholization was carried out at 90° C. for 5 h.

[0111] The above operations all involve stirring at a speed of 300 r / min, and an inert gas (nitrogen) is used for protection throughout the process.

[0112] This is followed by filtration and washing, wherein the washing step is carried out with deionized water.

[0113] Then, spray drying was performed under the protection of a nitrogen atmosphere at a drying rate of 1 kg / h at 200° C. to obtain a first precursor with a particle size of 8 μm.

[0114] S2. Preparation of the second precursor:

[0115] (1) Reduction: At 550°C, 1 L kg -1 ·min -1 With a ventilation volume of , hydrogen is passed for 120 min to reduce the first precursor.

[0116] (2) In-situ growth of carbon nanotubes: The product obtained in step (1) was treated in an acetylene atmosphere, wherein the acetylene flow rate was 2 L·kg -1 min -1 , time is 120min, temperature is 550℃.

[0117] (3) Pickling: Pickling is performed several times with 1 mol / L hydrochloric acid, wherein the mass ratio of hydrochloric acid to the product obtained in step (2) is 10:1 in each pickling, and the material is washed until no transition metal is present on the surface of the material and the magnetic foreign matter impurities are below 10 ppm.

[0118] (4) Drying: The acid-washed product was mixed with 10 times the mass of deionized water and then spray-dried to obtain a second precursor with a particle size of about 8 μm.

[0119] S3, Carbon coating

[0120] Acetylene is used to perform a vapor deposition reaction on the second precursor, and carbon is coated on the surface of the second precursor to obtain the final silicon-carbon material; wherein the ventilation volume of acetylene is 2L·kg -1 min -1 , time is 480min, temperature is 550℃.

[0121] Embodiment 2-9

[0122] On the basis of Example 1, only the corresponding steps and parameters in step S1 are changed according to Table 1, and the remaining steps and parameters are the same as Example 1, to prepare the silicon-carbon materials of Examples 2-9.

[0123] Table 1

[0124]

[0125] Comparative Example 1

[0126] On the basis of Example 1, the porous carbon-loaded silicon substrate obtained in step S0 is directly subjected to step S2 (preparation of a second precursor) and step S3 (carbon coating) to obtain the final silicon-carbon material.

[0127] Comparative Example 2

[0128] On the basis of Example 1, only step S1 is changed to the following steps:

[0129] In 10kg of deionized water, add 100g of complexing agent sodium citrate, add 0.8mol of ferrous sulfate, add 0.4mol of ferric chloride, and then add 1kg of ammonia water with a concentration of 5%, and the drop rate is 10mL / min. After the dropwise addition is completed, alcoholization is carried out at 90°C for 5h. Then 1kg of the porous carbon-loaded silicon substrate prepared in step S0 is added and impregnated for 5 hours. Subsequently, spray drying is carried out under the protection of a nitrogen atmosphere, and spray drying is carried out at a drying rate of 1kg / h at 200°C to obtain a first precursor with a particle size of 8μm.

[0130] The remaining steps and parameters are the same as in Example 1.

[0131] Comparative Example 3

[0132] On the basis of Example 1, only the corresponding steps and parameters in step S1 were changed according to Table 1, and the remaining steps and parameters were the same as Example 1, to obtain the silicon-carbon material of Comparative Example 3.

[0133] Comparative Example 4

[0134] On the basis of Example 1, only the corresponding steps and parameters in step S1 were changed according to Table 1, and the remaining steps and parameters were the same as Example 1, to obtain the silicon-carbon material of Comparative Example 4.

[0135] Comparative Example 5

[0136] In step S0 (i.e., preparation of porous carbon-loaded silicon substrate), the preparation of porous carbon in step (3) is not performed, and on the basis of Example 1, the corresponding steps and parameters in step S1 are changed according to Table 1, and the remaining steps and parameters are the same as Example 1, to obtain the silicon-carbon material of Comparative Example 5.

[0137] Effect Example

[0138] The following effect tests were performed on the intermediate products and the final silicon-carbon materials in Examples 1-9 and Comparative Examples 1-5 respectively:

[0139] 1. The obtained silicon-carbon material is used for relevant performance tests of batteries

[0140] (1) Button battery preparation

[0141] Preparation of negative electrode slurry and pole piece: The negative electrode formula is designed as CMC:PAA:SBR:SP:CNTs:silicon-carbon material:graphite=1:3:1:0.1:0.1:8:86.8 (by mass ratio). The negative electrode slurry preparation process is graphite→CMC→SP→CNTs→silicon-carbon material. After dispersing for 3 hours with a planetary disperser at a rotation speed of 300r / min and a revolution of 1000r / min, 80% deionized water is injected at one time and dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 600r / min. PAA is added and dispersed for 1 hour at a rotation speed of 500r / min and a revolution of 500r / min. Finally, SBR is added and dispersed for 1 hour at a rotation speed of 300r / min and a revolution of 300r / min. The coated current collector is 8 μm thick copper foil, coated on one side, with the coated side facing the negative electrode of the button battery, and the thickness of the active material coated on one side is 40 μm, with a compaction density of 1.7 g / cm 3 , where the coating speed is 40 cm / s, the post-baking temperature is 80°C, and the drying time is 400s.

[0142] Battery electrolyte preparation: The electrolyte composition, by mass percentage, is: EC 10%, PC 15%, DEC 20%, PP 30%, LiPF6 15%, FEC 6%, PS2.5% and LiODFB 1.5%.

[0143] Half-cell preparation: The positive electrode uses the above single-piece negative electrode plate, the negative electrode uses a lithium sheet, 0.5g of the above electrolyte, assembled into a CR2450 button cell, and the voltage serial port uses 0-1.5V. The entire battery is assembled in a glove box to avoid contact with air.

[0144] (2) Test parameters and steps

[0145] ① Cycle failure number, using Xinwei CT-4008Q-5V6A

[0146] 0.1C 0.8V gram capacity: According to the above steps, for each silicon-carbon material, CR 2450 button batteries were assembled respectively, and then constant voltage discharge was adopted. After discharging to 0.000v at 0.1V / h, it was charged to 0.8V at 0.1v / h, and the charging capacity was recorded. New CR2450 button batteries were reassembled and constant current charge and discharge tests were performed at a charging capacity of 0.1C. After discharging to 0v, it was charged to 0.8v. After obtaining the capacity, the gram capacity at 0.1C 0.8V was obtained by the capacity / mass of active matter in the electrode.

[0147] 0.5C 0.8V cycle failure number (measured at 25℃ and 45℃ respectively):

[0148] The above button battery was discharged at a constant voltage of 0.1V / h to 0.000V, and then charged at 0.1V / h to 0.8V, and the charging capacity was recorded. A button battery was reassembled and a constant current charge and discharge test was performed at 0.5C with the charging capacity recorded. The battery was repeatedly charged and discharged from 0V to 0.8V, and the discharge capacity was recorded. The discharge was terminated when the discharge capacity was 60% of the gram capacity at 0.1C and 0.8V, and the number of cycles was recorded.

[0149] 1C 0.8V cycle failure number (measured at 25℃ and 45℃ respectively):

[0150] The above button battery was discharged at a constant voltage of 0.1V / h to 0.000V, and then charged at 0.1V / h to 0.8V, and the charging capacity was recorded. A button battery was reassembled and a constant current charge and discharge test was performed at 1C with the charging capacity recorded. The battery was repeatedly charged and discharged from 0V to 0.8V, and the discharge capacity was recorded. The discharge was terminated when the discharge capacity was 60% of the 0.1C, 0.8V capacity, and the number of cycles was recorded.

[0151] ②Rate retention rate

[0152] 25℃ different rate retention rate (%): at 25℃, 1C rate cycle failure number / 0.5C rate cycle failure number.

[0153] 45℃ different rate retention rate (%): at 45℃, 1C rate cycle failure number / 0.5C rate cycle failure number.

[0154] 0.5C hot box cycle retention rate (%): 0.5C 45℃ cycle failure number / 0.5C 25℃ cycle failure number.

[0155] 2. Physical and chemical properties test of the intermediate products and silicon-carbon materials themselves

[0156] (1) Tap density: Aode-301 tap density produced by Dandong Aode Instrument Co., Ltd.

[0157] (2) BET test (specific surface area test) and full pore test: performed using ASAP2020 from Micromeritics;

[0158] (3) The test method or test equipment for compaction density is: punch the electrode into a unit circle, test the weight, subtract the weight of the copper foil, and divide it by the thickness to obtain the compaction density.

[0159] (4) Particle size test: The D50 particle size was tested using a laser particle size analyzer.

[0160] (5) Carbon content test: Use high-frequency carbon-sulfur analyzer (model DK-606).

[0161] (6) Raman spectroscopy test: There are two characteristic peaks in the Raman spectrum curve of silicon-carbon materials, with the peak values ​​located at 1310-1360 cm -1 The peak between is the disorder peak (D peak); located at 1560~1610cm -1 The peak between the D peak and the G peak is the graphite peak (G peak). The integrated area ratio of the D peak to the G peak (ID / IG) can be used to characterize the disorder or graphitization degree of the silicon-carbon material. The smaller the ID / IG, the lower the disorder and the higher the graphitization degree, and the stronger the buffering effect of the obtained material on the expansion of silicon-intercalated lithium.

[0162] (7) Powder resistivity test: The test is conducted using a powder conductivity meter (model FT-8100) based on the four-probe test principle and the test standard is GB / T 1552-1995. A known amount of solid powder of the material to be tested is used to compress the volume to a set pressure value or pressure under hydraulic power, and the resistivity of the solid powder is measured online.

[0163] The results are shown in Tables 2 to 5 respectively.

[0164] As follows, Table 2 shows the corresponding test parameters of the first precursors obtained in Examples 1-9 and Comparative Examples 1-5 (wherein the effect data of Comparative Example 1 is the effect data of the porous carbon-supported silicon substrate obtained in the comparative example):

[0165] Table 2

[0166]

[0167] As shown below, Table 3 shows the corresponding test parameters of the intermediate product obtained after in-situ growth of carbon nanotubes in step S2 in Examples 1-9 and Comparative Examples 1-5:

[0168] Table 3

[0169]

[0170]

[0171] As follows, Table 4 shows the corresponding test parameters of the silicon-carbon materials obtained in Examples 1-9 and Comparative Examples 1-5:

[0172] Table 4

[0173]

[0174] As follows, Table 5 shows the corresponding test parameters of the silicon-carbon materials finally obtained in Examples 1-9 and Comparative Examples 1-5 after being used in CR2450 button batteries:

[0175] Table 5

[0176]

[0177] Generally speaking, silicon-carbon materials after growing carbon nanotubes tend to improve their conductivity, reduce ID / IG, increase specific surface area, reduce tap density and enhance supporting effect; among them, silicon-carbon materials grown on single-walled carbon nanotubes can have the following differences in effects compared to those grown on multi-walled carbon nanotubes: higher conductivity (lower resistivity); lower ID / IG, higher degree of graphitization; and larger specific surface area.

[0178] From the above results, it can be seen that when the carbon nanotubes are grown in situ, the silicon-carbon materials obtained in Examples 1-9 have lower resistivity, lower ID / IG, larger specific surface area and lower tap density than Comparative Example 1, indicating the effective growth of carbon nanotubes, especially single-walled carbon nanotubes; and as the amount of metal salt increases, the growth of single-walled carbon nanotubes is also better, and the effect is optimal when the amount reaches Example 4. In addition, due to the coating of the carbon layer, the specific surface area and tap density of each embodiment tend to be consistent.

[0179] When the silicon-carbon material obtained in Examples 1-9 of the present invention is used in a battery, the single-walled carbon tubes have good elasticity and can effectively suppress the thickening of the sei film caused by the expansion of the silicon-carbon material, and the stable sei film can greatly improve the cycle performance of the obtained battery and can suppress the generation of lithium precipitation; in addition, the growth of the single-walled carbon tubes actually indirectly increases the thickness of the carbon layer, which is beneficial to suppress the problem of thermal runaway and improve the thermal cycle retention rate.

[0180] The metal salts used in Example 9 are cobaltous sulfate and cobalt chloride, which are inferior to iron salts in terms of thermal runaway inhibition and thermal cycle retention rate.

[0181] In Comparative Example 2, the traditional impregnation method easily leads to agglomeration of the catalyst, which in turn causes uneven dispersion of the grown carbon nanotubes and easy growth of multi-walled carbon tubes, resulting in significantly poor final conductivity, ID / IG, etc., as well as the cycle performance of the resulting battery.

[0182] In Comparative Examples 3-4, when only divalent iron or trivalent iron salts are used to prepare the catalyst, the generated metal oxide particles are relatively large, causing pore blockage of the porous carbon, making it difficult to elute when washing with deionized water, thereby resulting in significantly poorer related performance.

[0183] In Comparative Example 5, since no activation was performed before silicon deposition, the number of pores was significantly lower and the amount of silicon deposited was significantly reduced. Although the cycle and cycle retention rates of the final battery were significantly optimal, related effects such as conductivity and ID / IG were significantly reduced, as can be seen from the specific surface area in Tables 2-4.

Claims

1. A method for preparing a silicon-carbon material, characterized in that: The preparation method of the silicon-carbon material comprises the following steps: S1, a mixed solution containing a porous carbon-supported silicon substrate, a transition metal salt and a solvent, reacts with an alkaline reagent to obtain a first precursor; Wherein, the transition metal salt includes divalent salt and trivalent salt of transition metal; Wherein, the reaction is carried out under a protective atmosphere; S2, using a carbon source to perform chemical vapor deposition on the first precursor to in-situ grow carbon nanotubes to obtain a second precursor; S3. Carbon-coating the second precursor to obtain the silicon-carbon material.

2. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the transition metal salt includes one or more of an iron salt, a nickel salt and a cobalt salt; Preferably, in step S1, the transition metal salt comprises a divalent salt and a trivalent salt of iron; wherein the molar ratio of the divalent salt and the trivalent salt of iron is preferably (2-4):1; And / or, in step S1, the transition metal salt includes one or more of transition metal hydrochloride, transition metal sulfate, transition metal acetate and transition metal citrate; Preferably, the transition metal salt includes ferrous sulfate and ferric chloride; And / or, in step S1, the content of the transition metal salt is 0.03-0.3 mol / L, for example, 0.12 mol / L, and the content is the number of moles of the transition metal salt contained in 1 L of the solvent; And / or, in step S1, the mixed solution further comprises a complexing agent; Wherein, the complexing agent preferably includes an organic acid and a salt thereof, more preferably includes one or more of acetic acid, citric acid, EDTA and a salt thereof, for example, includes one or more of ferric acetate, sodium acetate, ferric citrate, sodium citrate and EDTA; Wherein, the mass ratio of the complexing agent to the porous carbon-supported silicon substrate is preferably 1:(5-1000), for example 1:

10.

3. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the alkaline reagent includes a weak base reagent and / or a strong base reagent, preferably ammonia water; Wherein, the concentration of the ammonia water is preferably 1-10%, for example 5%; And / or, in step S1, the mass ratio of the alkaline reagent to the mixed solution is (1-10):100; And / or, in step S1, the alkaline reagent is added dropwise to the mixed solution, and the dropping speed of the alkaline reagent is 5-50 mL / min, for example, 10 mL / min; And / or, in step S1, the solvent is deionized water; And / or, in step S1, the mass ratio of the porous carbon-supported silicon substrate to the solvent is 1:(5-50), for example 1:10; And / or, in step S1, the protective atmosphere includes one or more of an inert atmosphere, a reducing atmosphere and a carbon dioxide atmosphere, for example, includes one or more of nitrogen, argon, helium, hydrogen and carbon monoxide; And / or, in step S1, the reaction is carried out under stirring conditions; Wherein, the stirring speed is preferably 100-1000r / min, for example 300r / min.

4. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the surface of the porous carbon-loaded silicon substrate is coated with a passivation layer; the passivation layer preferably comprises a carbon layer and / or an oxide layer; Preferably, the preparation method of coating the passivation layer is to use a deposition gas for chemical vapor deposition; Wherein, the deposition gas preferably includes a carbon source, and more preferably also includes a protective gas; the carbon source preferably includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates; the protective gas preferably includes one or more of nitrogen, helium and argon; The ventilation volume of the deposition gas is preferably 0.1-10 L·kg -1 ·min -1 , for example 5L·kg -1 ·min -1 ; Wherein, the chemical vapor deposition time is preferably 2-20h; The temperature of the chemical vapor deposition is preferably 400-800°C, such as 500°C.

5. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the reaction further includes alcoholization and drying steps; Wherein, the alcoholization temperature is preferably 60-100°C, for example 90°C; Wherein, the alcoholization time is preferably 3-12h, for example 5h; Wherein, the drying temperature is preferably 100-250°C, for example 200°C; Wherein, the drying is preferably carried out in an inert atmosphere; the inert atmosphere preferably includes one or more of nitrogen, helium and argon; Wherein, the drying speed is preferably 0.1-10kg / h, for example 1kg / h; Wherein, the drying method is preferably spray drying or vacuum drying; And / or, in step S1, the particle size of the first precursor is 4-20 μm, for example, 8 μm.

6. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, before the chemical vapor deposition, the step of reducing the first precursor is also included; Wherein, the reduction temperature is preferably 400-800°C, for example 550°C; The reduction is preferably carried out in a reducing atmosphere; the reducing atmosphere is preferably hydrogen; the ventilation volume of the reducing atmosphere is preferably 0.1-10 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 ; The reduction time is preferably 30-300 min, for example 120 min.

7. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the carbon source includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates; And / or, in step S2, the ventilation volume of the carbon source is 2-10 L·kg -1 ·min -1 ; And / or, in step S2, the chemical vapor deposition time is 60-180 min, for example, 120 min; and / or, in step S2, the temperature of the chemical vapor deposition is 500-700° C., for example, 550° C.; And / or, in step S2, the chemical vapor deposition further includes the steps of pickling and drying; Wherein, the pickling step is preferably carried out with hydrochloric acid; the mass ratio of the hydrochloric acid to the product obtained by the reaction is (5-50):1, for example 10:1; Wherein, the drying method is preferably spray drying or vacuum drying; And / or, in step S2, the particle size of the second precursor is 4-20 μm, for example, 8 μm.

8. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S3, the carbon coating comprises the following steps: chemical vapor deposition of the second precursor using a carbon source; Wherein, the carbon source preferably includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates; The ventilation volume of the carbon source is preferably 0.1-10 L kg -1 ·min -1 , for example 2L·kg -1 ·min -1 ; Wherein, the chemical vapor deposition time is preferably 300-600 min, for example 480 min; The temperature of the chemical vapor deposition is preferably 400-800°C, such as 550°C.

9. A silicon-carbon material, characterized in that: The silicon-carbon material is prepared by the method for preparing the silicon-carbon material according to any one of claims 1 to 8.

10. Use of the silicon-carbon material according to claim 9 in an electrochemical device.